Australia (Northern Territory) - The Nature Conservancy (Symphony in the Flint Hills, 2015)
Covering more than 247 million acres, an area larger than California, Colorado, and New Mexico combined, Northern Australia is one of the few remaining largescale natural areas left on Earth.
Keywords: animals; native; grassland; natural; tropical; savanna; history; ancient; vegetation